Expanding the time interval between ovulation triggering and oocyte injection: does it affect the embryological and clinical outcome?. Issue 3 (24th December 2020) - Vandenberghe, L T M; Santos-Ribeiro, S; De Munck, N; Desmet, B; Meul, W; De Vos, A; Van de Velde, H; Racca, A; Tournaye, H; Verheyen, G
Abstract: STUDY QUESTION: Is the time interval between ovulation triggering and oocyte denudation/injection associated with embryological and clinical outcome after ICSI? SUMMARY ANSWER: Expanding the time interval between ovulation triggering and oocyte denudation/injection is not associated with any clinically relevant impact on embryological or clinical outcome. WHAT IS KNOWN ALREADY: The optimal time interval between ovulation triggering and insemination/injection appears to be 38–39 h and most authors agree that an interval of >41 h has a negative influence on embryological and clinical pregnancy outcomes. However, in ART centres with a heavy workload, respecting these exact time intervals is frequently challenging. Therefore, we questioned to what extent a wider time interval between ovulation triggering and oocyte injection would affect embryological and clinical outcome in ICSI cycles. STUDY DESIGN, SIZE, DURATION: A single-centre retrospective cohort analysis was performed including 8811 ICSI cycles from 2010 until 2015. Regarding the time interval between ovulation triggering and oocyte injection, seven categories were considered: <36 h, 36 h, 37 h, 38 h, 39 h, 40 h and ≥41 h. In all cases, denudation was performed immediately prior to injection. The main outcome measures were oocyte maturation, fertilization and embryo utilization rate (embryos adequate for transfer or cryopreservation) per fertilized oocyte. Clinical pregnancy rate (CPR) and live birth rate (LBR) were considered as secondary outcomes. Utilization rate, CPR and LBR were subdivided into two groups according to the day of embryo transfer: Day 3 or Day 5. PARTICIPANTS/MATERIALS, SETTING, METHODS: During the study period, oocyte retrieval was routinely performed 36 h post-triggering except in the <36 h group. The interval of <36 h occurred only if OR was carried out before the planned 36 h trigger interval and was followed by immediate injection. Only cycles with fresh autologous gametes were included. The exclusion criteria were: injection with testicular/epididymal sperm, managed natural cycles, conventional IVF, combined conventional IVF/ICSI, preimplantation genetic testing and IVM cycles. Female age, number of oocytes, pre-preparation sperm concentration, post-preparation sperm concentration and motility, day of transfer, number of embryos transferred and quality of the best embryo transferred were identified as potential confounders. MAIN RESULTS AND THE ROLE OF CHANCE: Among the seven interval groups, adjusted mean maturation rates ranged from 76.4% to 83.2% and differed significantly ( P < 0.001). Similarly, there was a significant difference in adjusted mean fertilization rates (range 69.2–79.3%; P < 0.001). The adjusted maturation and fertilization rates were significantly higher when denudation/injection was performed >41 h post-triggering compared to 38 h post-triggering (reference group). Oocyte denudation/injection at <36 h post-triggering had no significant effect on maturation, fertilization or embryo utilization rates compared to injection at 38 h. No effect of the time interval was observed on CPRs and LBRs, after adjusting for potential confounders. When oocyte injection was performed before 36 h the adjusted analysis showed that compared to 38 h after ovulation triggering the chance of having a live birth tends to be lower although the difference was not statistically significant (odds ratio 0.533, 95% CI: 0.252–1.126; P = 0.099). Injection ≥41 h post-triggering did not affect LBR compared to injection at 38 h post-ovulation. LIMITATIONS, REASONS FOR CAUTION: As this is a large retrospective study, the influence of uncontrolled variables cannot be excluded. These results should not be extrapolated to other ART procedures such as IVM, conventional IVF or injection with testicular/epididymal sperm. WIDER IMPLICATIONS OF THE FINDINGS: Our results indicate that the optimal injection time window may be less stringent than previously thought as both embryological and clinical outcome parameters were not significantly affected in our analysis. This is reassuring for busy ART centres that might not always be able to follow strict time intervals. STUDY FUNDING/COMPETING INTEREST(S): No funding. The authors declare no conflict of interest related to the present study. TRIAL REGISTRATION NUMBER: N/A.